2020
DOI: 10.21203/rs.3.rs-33901/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

CERTL Reduces C16 Ceramide, Amyloid-β Levels and Inflammation in a Model of Alzheimer's Disease

Abstract: Background: Deregulation of ceramide and sphingomyelinlevels have been suggested tocontribute tothe pathogenesis of Alzheimer’s disease (AD).Ceramide transfer proteins (CERTs) are ceramide carriers, crucial for ceramide and sphingomyelin balance in cells.Extracellular forms of CERTs co-localize with amyloid-β (Aβ) plaques in AD brains. To date, the significance of these observations for the pathophysiology of AD remains uncertain.Methods: The plasmid expressing CERTL, the long isoform of CERTs, was used to stu… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 70 publications
(111 reference statements)
1
8
0
Order By: Relevance
“…These enzymes show differences in their levels of expression depending on the tissue, cell type and subcellular compartment [4][5][6][7]. Adding further complexity, numerous SM species exist that differ in the length and degree of unsaturation of their fatty acids, and these different species have distinct subcellular localization, metabolism and properties [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…These enzymes show differences in their levels of expression depending on the tissue, cell type and subcellular compartment [4][5][6][7]. Adding further complexity, numerous SM species exist that differ in the length and degree of unsaturation of their fatty acids, and these different species have distinct subcellular localization, metabolism and properties [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, lipidomic, metabolomic, and targeted approaches have identified pathways of lipids and enzymes of the sphingolipid metabolism that are altered early in the course of AD and contribute to the neuropathological alterations associated with AD. 1,[4][5][6] Sphingolipid metabolites like sphingosine-1-phosphate (S1P) have additionally been implicated in neuroinflammation and neurodegeneration. 1 Along these lines, previous longitudinal studies examining blood sphingolipids reported that high levels of multiple ceramide species predicted cognitive impairment among cognitively unimpaired individuals, 7 as well as memory decline, hippocampal volume loss, 8 and faster rates of cognitive decline among AD patients.…”
Section: Introductionmentioning
confidence: 99%
“…Ceramides are produced in the endoplasmic reticulum of neurons and glia, and transported from the endoplasmic reticulum to the trans-Golgi regions of these cells by ceramide transporter proteins (CERTs). 5 CERTs are ubiquitously expressed in the CNS, where they are involved in brain development and homeostasis and transport ceramide to membranes via its steroidogenic acute regulatory protein (StAR)-related lipid transfer domain. 2,5,10,11 Specifically, they are known to transfer ceramide C14, C16, C18, and C20 chains.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations